Polymorphisms in the maternal sex steroid pathway are associated with behavior problems in male offspring - Miodovnik, Amir (2012)
OBJECTIVE: Slight perturbations in maternal sex steroid production and metabolism may interfere with normal fetal neurodevelopment. The balance of maternal estrogens and androgens may have direct fetal effects, may influence the fetal hypothalamic-pituitary-gonadal axis or may alter local hormonal activity within the fetal brain. We investigated maternal functional polymorphisms of CYP17, CYP19 and CYP1B1, which control three major enzymatic steps in sex steroid biosynthesis and metabolism, in relation to childhood behaviors. METHODS: The Mount Sinai Children’s Environmental Health Study enrolled a multiethnic urban pregnancy cohort from 1998–2002 (n = 404). DNA was obtained from maternal blood (n=149) and from neonatal cord blood (n=53). At each visit, mothers completed the Behavior Assessment System for Children (BASC), a parent-reported questionnaire used to evaluate children for behavior problems. We focused on problem behaviors more commonly associated with ADHD (hyperactivity, attention problems, externalizing behaviors, conduct disorder, poor adaptability) to see if maternal genetic variants in sex steroid production and metabolism influence sexually-dimorphic behaviors in offspring. RESULTS: The more active gene variants were significantly associated with Attention Problems and poorer Adaptive Skills in male compared to female offspring. The CYP19 variant allele was also significantly associated with worse scores for boys on the Hyperactivity, Externalizing Problems Composite and Adaptive Skills Composite scales (p < 0.05). CONCLUSION: We observed maladaptive behaviors in the male offspring of mothers who carried functional polymorphisms in the sex steroid pathway. The strongest associations were in domains commonly affected in Attention Deficit-Hyperactivity Disorder.